The biogeography and conservation biology of Spiranthes romanzoffiana Chamisso - Lupton, Darach (Trinity College (Dublin, Ireland). Department of Botany, 2008)
The aim of this research was to gather baseline data on Irish populations of Spiranthes romanzoffiana, a species with an uneven amphi-Atlantic distribution. The species is widespread in North America. In Europe, populations are confined to the west and north east of Ireland and to the Hebridean islands in western Scotland. S. romanzoffiana is protected in the Republic of Ireland by the Wildlife Act (1967), under the Flora Protection Order [SI 94 of 1999] and is an Irish Red List species. Four sample populations in the Republic of Ireland were studied to determine the ecology, population, reproductive and pollination biology of S. romanzoffiana. Threats to the species' persistence were assessed at each site. Amplified Fragment Length Polymorphism (AFLP) and chloroplast microsatellite markers were used to determine the level of genetic diversity and differentiation within and between Irish, Scottish and North American samples.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin